Paratasmanicola inerma gen. et. sp. nov. from Tasmania (Hemiptera: Heteroptera: Rhyparochromidae) - Malipatil, M. B.; O’donnell, J. E. (Zootaxa, 2022)
Paratasmanicola inerma gen. et. sp. nov. is described as the second genus of tribe Stygnocorini (Hemiptera: Heteroptera: Rhyparochromidae: Rhyparochrominae) from Tasmania Australia, and compared with related genera to provide diagnoses, and notes on zoogeographic implications based on these genera as applying to the tribe Stygnocorini. Additionally, the new genus Paratasmanicola is compared with another Tasmanian rhyparochromid Getes Bergroth, 1916 to attempt to resolve the current uncertain tribal status of the latter genus.